Neck Muscles and Content of Carotid Artery as Reference Tissue for Strain Ratio - a Novel Approach to Improve the Diagnostic Performance of Thyroid Elastography - Kratky, J; Vitkova, H; Bartakova, J; Lukas, J; Jiskra, J (Experimental and clinical endocrinology & diabetes, 2016)
Measurement of thyroid nodule stiffness by strain elastography already showed promising results. The aim of our study was to evaluate the diagnostic performance of elastography in predicting thyroid cancer by determination of strain ratio comparing nodule stiffness with thyroid tissue and surrounding neck tissues as well (carotid artery, neck muscles). Totally, 310 thyroid nodules in 275 patients were examined by conventional ultrasound and elastography prior to aspiration biopsy. 22(7.1%) thyroid carcinomas were histologically confirmed and included in the study. 39 benign nodules (27 confirmed by histology and 12 with benign cytology and at least 2 years stable ultrasound finding) formed control group. Elastography was evaluated qualitatively using 6-grade score and strain ratio to surrounding thyroid tissue, carotid artery and neck muscles was determined. High-risk elastographic score (4,5) was more frequent in carcinomas (67%) compared with benign nodules (11%, p<0.001). Significant differences in distribution of strain were found in all studied parameters except comparison with thyroid tissue in transversal dimension. Strain ratio comparing the stiffness with neck muscles had a higher negative predictive value than elastographic score and conventional ultrasound (92 vs. 83 and 82% respectively). Moreover, the combination of ultrasound and strain ratio to neck muscles increased sensitivity and negative predictive value to 100%. Our results suggest, that strain ratio to neck muscles in combination with ultrasound seems to have good sensitivity and negative predictive value for predicting thyroid cancer and may be beneficial in cases when comparison to surrounding thyroid tissue is problematic (Hashimoto thyroiditis, multinodular goiter, large nodule).
Keywords: dospělí; Elasticity Imaging Techniques; Female; arteriae carotides; krční svaly; Adult; ženské pohlaví; uzly štítné žlázy; lidé; elastografie; Neck Muscles; Carotid Arteries; Male; Aged; štítná žláza; Thyroid Gland; lidé středního věku; Thyroid Nodule; senioři; mužské pohlaví; Middle Aged; Humans